Information and Decision-Making Processes in Crisis Situations - Skelnik, Klaudia (Roczniki Nauk Społecznych, 2026)
The article addresses the issue of information and decision-making processes taking place in crises. There is no integration between theoretical models of information and the practical aspects of crisis response; the administrative approach is excessively formal, neglecting cultural and psychological factors. The paper analyses the importance of information as a strategic resource, the determinants of information quality and their impact on the rationality of decisions made under time constraints and uncertain circumstances. A review of Polish and international literature has been conducted, accompanied by a methodological approach based on content analysis, comparative and case studies. The findings indicate that the key element of effective crisis management is minimising the information–decision gap, selecting relevant data, and safeguarding against disinformation. Accurate, up-to-date, and relevant information constitutes the foundation of making accurate decisions in situations threatening public safety.